Sodium and Sugar Intake Comparison Among Participants of the USDA National School Lunch Program Versus Non-Participants Based on 2015–2016 NHANES Survey. (29th May 2020) - Connelly, Jeneene; Palacios, Cristina; Campa, Adriana; Gonzalez, Nicholas; De La Torre, Karla; Panchana, Xavier
Abstract: Objectives: The National School Lunch Program (NSLP) surveys the overall health and well-being of participants nationwide. To address rising obesity rates in the US, the USDA implemented revisions in 2010 to the NSLP targeting sodium and sugar intake reduction. Our objective was to compare intake of sodium and sugar between NSLP participants and non-NSLP participants. Methods: Data from 2015–2016 NHANES survey were analyzed, which is after the implementations of the USDA revisions. All children (4–15 years) with two 24-hr dietary recalls were included. Mean intake for sugar and sodium were computed between the 2 recalls. NSLP participants were those who reported 2–5 school lunches per week whereas those reporting one school lunch per week or none were considered as not participating. Analyses were stratified by the following ages groups: 4–8y; 9–13y; and 14–15y. ANCOVA, adjusted for gender, was used to compare normalized intakes of sugar and sodium. Results: A total of 1370 children were included (49% were females). Sugar intake was similar between NSLP or non-NSLP participants in children 4–8y. In children 9–13y, sugar intake was higher in NSLP participants (101 ± 2.31 g/d) versus non-NSLP participants (95.2 ± 1.94 g/d; P  = 0.010) but lower in children 14–15y in NSLP participants (95.7 ± 2.44 g/d) versus non-NSLP participants (106 ± 2.67 g/d; P  = 0.022). Sodium intake was higher in NSLP participants (2731 ± 8.64 mg/d) versus non-NSLP participants (2583 ± 9.69 mg/d; P  = 0.020) in children 4–8y and also in children 9–13y (NSLP participants 3097 ± 10.4 mg/d; non-NSLP participants 2852 ± 8.07; P  < 0.001) but only lower among NSLP participants (3102 ± 10.3 mg/d) versus non-NSLP participants (3240 ± 12.4 mg/d; P  = 0.002) in children 14–15y. Conclusions: The effects of the new NSLP recommendations are conflicting compared with children not participating in the program. Sugar and sodium intakes were generally higher among NSLP participants between the ages of 9–13 years old. This suggests that despite recommendations to reduce sodium and sugar intake among school children, these nutrients might still be of concern. In short, this study indicates that a greater investment on education is needed and that further research should assess the effect of changes on NSLP recommendations through time. Funding Sources: Florida International University.